2022
DOI: 10.1128/mbio.03272-21
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Extracellular Vesicles Are Involved in Intraspecies Intracellular Communication

Abstract: Here, we report a study about extracellular vesicles (EVs) as communication mediators in fungi. Our results demonstrated the role of EVs from Candida albicans , Aspergillus fumigatus , and Paracoccidioides brasiliensis regulating the expression of target genes and phenotype features.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…From this projection, the autoregulatory function of fungal EVs in the cellular metabolism and cell communication, which reinforces the role of RNA-EVs in interkingdom and intraspecies signaling, is evident. Indeed, a recent study demonstrated the regulatory function of fungal EVs in fungal gene expression, governing the pathophysiological attributes of the pathogenic fungi C. albicans, A. fumigatus , and P. brasiliensis [ 54 ]. However, whether exonic sRNAs could be mature miRNAs exported by fungal EVs to confer faster adaptive responses requires further study and elucidation.…”
Section: Rna Content Of Fungal Evsmentioning
confidence: 99%
“…From this projection, the autoregulatory function of fungal EVs in the cellular metabolism and cell communication, which reinforces the role of RNA-EVs in interkingdom and intraspecies signaling, is evident. Indeed, a recent study demonstrated the regulatory function of fungal EVs in fungal gene expression, governing the pathophysiological attributes of the pathogenic fungi C. albicans, A. fumigatus , and P. brasiliensis [ 54 ]. However, whether exonic sRNAs could be mature miRNAs exported by fungal EVs to confer faster adaptive responses requires further study and elucidation.…”
Section: Rna Content Of Fungal Evsmentioning
confidence: 99%
“…In addition, their experiments also suggested that EVs stimulated C. albicans growth, a result not exploited but consistently observed in our current work. These differences might have resulted from the use by Bitencourt et al ( 59 ) of a distinct C. albicans strain (ATCC 64548) and a different culture condition (YPD medium), which could modify the EV composition, as previously reported ( 60 ). Moreover, their experimental conditions were limited to 4 h of filamentation, when the morphological impact of EVs was just initiating in our experiments.…”
Section: Discussionmentioning
confidence: 94%
“…Altogether, these results indicate that C. albicans EVs carry a group of terpenes and fatty acids able to regulate growth and morphogenesis in C. albicans . A recent work published by Bitencourt and colleagues ( 59 ) also suggested that fungal EVs could be involved in fungal intraspecies communication and could regulate C. albicans dimorphism. However, in contrast with our results, those authors demonstrated that C. albicans EVs produced by yeasts induced filamentation, although EVs from hyphae exhibited a more prominent effect.…”
Section: Discussionmentioning
confidence: 97%
“…In this model, EVs have immunostimulatory activity (4) and vaccinal potential (5). Cryptococcal EVs are also required for fungal virulence (6) and intraspecies communication (7).…”
Section: Introductionmentioning
confidence: 99%